The Future of Arab Citizenship in Israel: Jewish-Zionist Time in a Place with No Palestinian Memory - Jabareen, Hassan (Hagar: Studies in Society and Culture, 2003)
This article attempts to contribute to a further understanding of “homeland minority group rights. ” The article distinguishes between the characteristics and demands of homeland groups, national minorities, cultural minorities, and immigrant groups. The author argues that in Israel, numerous Supreme Court decisions, as well as primary legislation, show that the state is, at most, prepared to relate to Palestinian citizens of Israel as possessing a status that is similar to that of diverse ethnic migrant groups. For these groups, citizenship rights are generally limited to the civil-political sphere, with some recognition of cultural rights, on the condition that such recognition will not adversely impact on the ideological structure of the state. Based on this model, for Palestinian citizens of Israel, rights are made conditional by renouncing components of their Palestinian identity, and instead assuming the “Israeli Arab” identity that includes acceptance of the ideological values of Zionism. The author contends that this model’s problematic nature, in respect to equality, is an upshot of the state’s failure to recognize Palestinians who are Israeli citizens as persons indigenous to their homeland. The main case study used to theorize these issues is the Supreme Court’s important precedent-setting judgment in Qa’dan.